TEACHERS PERSPECTIVES REGARDING THE IMPLEMENTATION OF MERDEKA BELAJAR IN ENGLISH CLASS: AN EXPLORATORY STUDY IN INDONESIAN CONTEXT - 'Ainiyah, Aylul Fajrinniar; Prasetyarini, Aryati (FKIP UNISKA, 2024)
This research was conducted to determine English teachers' perspectives, efforts, and challenges in implementing the Merdeka Belajar (Freedom to Learn) Curriculum in the classroom. Anchored from the interpretative paradigm, the study applied qualitative design using observation and interview to collect the data. The participants were the seventh and eighth -grade English teachers at one of the state Islamic schools in East Java. Data were obtained through observation and interviews. The data is analyzed using content analysis techniques and then validated using the data triangulation method. The results of the research showed that teachers had four perspectives, four efforts, and four challenges. The teachers' perspectives included: (1) The Freedom to Learn Curriculum encourages motivation and creativity, (2) The effectiveness of the curriculum, (3) Encouraging independence, and (4) Differentiated learning models. The teachers' efforts included: (1) Creating teaching materials, (2) Giving quizzes, (3) Making students work in groups, and (4) Providing feedback. The teachers' challenges included: (1) Adjusting to the new curriculum, (2) Unsupportive signals, (3) Adapting teaching to students' characters and needs, and (4) Difficulty in maintaining student engagement in the classroom. The conclusion of this research is that the teachers' perspectives were conveyed positively, and the teachers have made creative efforts for self-learning.